Grenada : Fifth Review Under the Extended Credit Facility, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Grenada's Fifth Review Under the Extended Credit Facility (ECF), Request for Modification of Performance Criteria, and Financing Assurances review. Overall program implementation remains solid. All quantitative performance criteria for the Fifth Review were met. Some structural benchmarks have been delayed, but there has been corrective action. The authorities have advanced reforms to strengthen tax administration, improve public finance management, and bolster the business environment. The IMF staff supports the completion of the Fifth Review under the ECF arrangement.